Sociohistorical Narrative of Calligraphic Art in Pakistan - Dr Rafya Tahir; Dr Syed Farjood Ailya Rizvi (بازیافت)
The development of calligraphic art in Pakistan is affected by social and historical factors. Because of the religious connotations attached to this art, its acceptance in the art circles is contentious. This qualitative paper focuses on calligraphic art done in Arabic script which developed in Pakistan after 1947.  Exploratory research design is used for data collection.  A narrative and descriptive approach is adopted for data presentation and analysis This paper explores calligraphic art from a historical perspective and aims to bring into light its existing status in the contemporary art circles of Pakistan.  The results show a substantial inclination toward religious attachment in general perception and a reluctance of accepting it as a truly expressive art in artistic circles.